Thermal optimization of circular bodies submitted to an intense heat flux using constructal design - Vergara, Leandro Cavalheiro; Santos, Elizaldo Domingues dos; Rocha, Luis Alberto Oliveira (VETOR - Revista de Ciências Exatas e Engenharias, 2010)
The present work studies the optimization of a circular body with an intense heat flux by Constructal Design. The problem concerns the minimization of the global thermal resistance of a three-dimensional structure submitted to an intense uniform heat flux, which is cooled through micro-channels inserted in the circular body. For the optimization the body and the channels volumes are kept constants, while the geometrical configuration varies. Two geometric configurations were studied: radial and with one level of bifurcation - the first construct. The conservation equations of mass, momentum and energy are solved using a commercial package based on the finite volume method. For the radial configuration the system was successfully optimized as function of the number of ducts intruded into the body. For the bifurcated configuration Constructal Design led to a double optimization: one as function of the angle between the branches on the bifurcation () and other as function of the ratio between the length of a single duct (L0) and the radius of the circular domain (L).